Host Response to Staphylococcus epidermidis Colonization and Infections - Nguyen, Thuan H.; Park, Matthew D.; Otto, Michael (Frontiers in Cellular and Infection Microbiology, 2017)
The majority of research in the Staphylococcus field has been dedicated to the understanding of Staphylococcus aureus infections. In contrast, there is limited information on infections by coagulase-negative Staphylococci (CoNS) and how the host responds to them. S. epidermidis, a member of the coagulase-negative Staphylococci, is an important commensal organism of the human skin and mucous membranes; and there is emerging evidence of its benefit for human health in fighting off harmful microorganisms. However, S. epidermidis can cause opportunistic infections, which include particularly biofilm-associated infections on indwelling medical devices. These often can disseminate into the bloodstream; and in fact, S. epidermidis is the most frequent causes of nosocomial sepsis. The increasing use of medical implants and the dramatic shift in the patient demographic population in recent years have contributed significantly to the rise of S. epidermidis infections. Furthermore, treatment has been complicated by the emergence of antibiotic-resistant strains. Today, S. epidermidis are major nosocomial pathogens posing significant medical and economic burdens. In this review, we present the current understanding of mechanisms of host defense against the prototypical CoNS species S. epidermidis as commensals of the skin and mucous membranes, and during biofilm-associated infection and sepsis.